Romania : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Romania's economic recovery has become more entrenched and broad based, with private consumption picking up on the back of rising real disposable income. At the same time, inflation has decelerated substantially over the past two years and a negative output gap persists. The banking sector has considerably reduced nonperforming loans, though they remain high, and private sector credit has fallen since 2013. Growth is projected to remain robust in a low inflation environment. Raising growth prospects over the longer term requires continuity of sustainable macroeconomic policies, underpinned by stronger fiscal and regulatory institutions, and a more stable and predictable business environment, which is crucial for investor confidence.